2013
DOI: 10.5830/cvja-2013-065
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience of repair of pectus excavatum and carinatum deformities

Abstract: BackgroundWe present the results of surgical correction of pectus excavatum (PE) and pectus carinatum (PC) deformities in adults, and also report a new method of sternal support used in surgery for PE deformities.MethodsWe present the results of 77 patients between the ages of 10 and 29 years (mean 17) with PE (n = 46) or PC (n = 31) deformities undergoing corrective surgery from 2004 to 2011, using the Ravitch repair method. Symptoms of the patients included chest pain (15%) and tachycardia (8%). Three patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…In all patients, improvements in exercise tolerance with less dyspnea was reported after surgery: 74 had good physical activity at 6 months postoperatively, but 2 pectus excavatum patients and 1 pectus carinatum patient had a recurrence. 7 In our study, the most common symptom was exercise dyspnea, and 31 patients showed improvement in physical activity and cosmetic results postoperatively; 2 patients had recurrence of pectus excavatum.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In all patients, improvements in exercise tolerance with less dyspnea was reported after surgery: 74 had good physical activity at 6 months postoperatively, but 2 pectus excavatum patients and 1 pectus carinatum patient had a recurrence. 7 In our study, the most common symptom was exercise dyspnea, and 31 patients showed improvement in physical activity and cosmetic results postoperatively; 2 patients had recurrence of pectus excavatum.…”
Section: Discussionmentioning
confidence: 47%
“…Ravitch 6 was the pioneer of modern treatment for these deformities, pectus excavatum being corrected by resection of the elongated cartilage. In a retrospective study by Oncel and colleagues, 7 77 patients with pectus deformities were studied. The mean age of these patients was 17 years (range 10-22 years).…”
Section: Discussionmentioning
confidence: 99%
“…Although most institutions perform a thorough evaluation of the patient, unfortunately few papers have reported full data on postinterventional spirometry and exercise performance [ 24–26 ] . Moreover, follow-up examinations were mainly performed as clinical evaluations, or via telephone or retrospective mail questionnaires, thus not providing objective data [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their Letter to the Editor, Oncel and colleagues [4] noted that our recommendation that patients with a PI greater than 4.0, an asymmetrical defect, and calcified costal cartilages should not undergo a Nuss procedure for correction of pectus excavatum is contrary to their practice of successful Nuss procedures, in which "most patients with a pectus index of 6.0" and is superior to open surgical techniques in every aspect. Oncel and colleagues [4] referenced an article from their institution published in 2013 [5]. That series of 77 patients with pectus deformities was from 2004 through 2011 and they underwent repair with an open Ravitch procedure and a K-wire for posterior sternal support.…”
Section: Reply To the Editormentioning
confidence: 99%
“…Concomitant pharmacologic treatments have influences on signalling pathways, and indeed glucocorticoids have been used as antiinflammatory agents clinically modulating signalling cascades [3]. However, methylprednisolone does not appear to alter the effect of CPB on p38 MAP kinase phosphorylation in right atrial tissue [4] and other drugs commonly given to cardiothoracic surgical patients (eg, aspirin [5], statins [6], angiotensin converting enzyme inhibitors [7], antidiabetes medication [8] and analgesics [9]), have influences on immune signalling.…”
Section: Reply To the Editormentioning
confidence: 99%